1953
DOI: 10.1161/01.res.1.4.321
|View full text |Cite
|
Sign up to set email alerts
|

The Metachromatic Activity of Urine Following the Injection of Heparin

Abstract: Heparin was injected in man, dog, rabbit and sheep and the metachromatic activity (MA) of the urine measured directly or after precipitation with benzidine. The presence and amount of MA in the urine depended on route, size and time relations of the injection, but generally was much less than the MA of the heparin injected. An excretion product, uroheparin, has been described. It is concluded that following injection heparin may be ( a ) destroyed by heparinase, ( b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1954
1954
2008
2008

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The Astrop fraction of urine (24) and the metachromatic urinary "heparin" (25), prepared by methods which involve heating with ammonia, are certain to contain variable quantities of this mucoprotein or its alkaline degradation products, unless the NaClinsoluble residue is removed prior to heating and treatment at pH 12 or more.…”
Section: Discussionmentioning
confidence: 99%
“…The Astrop fraction of urine (24) and the metachromatic urinary "heparin" (25), prepared by methods which involve heating with ammonia, are certain to contain variable quantities of this mucoprotein or its alkaline degradation products, unless the NaClinsoluble residue is removed prior to heating and treatment at pH 12 or more.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of heparin it has been suggested that inactivation is effected by an enzyme "heparinase" (Jaques, 1940). However, this enzyme has been isolated only from rabbit liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, this enzyme has been isolated only from rabbit liver. An attempt to obtain similar material from beef liver was unsuccessful (Jaques and Keeri-Szanto, 1952). The enzyme from rabbit liver was found to show lack of specificity in that, in addition to acting upon heparin derived from various species, certain synthetic polysaccharides were also degraded.…”
Section: Discussionmentioning
confidence: 99%
“…The method of Astrup (2) was followed closely. 3 In patients eating diets which impose rigid sodium restriction, it has been found necessary to add additional salts to the urine prior to using benzidine HCI in order to obtain maximal precipitation of acid mucopolysaccharides. For the sake of uniformity, this step has been 3 By this method, not less than 80 per cent of added heparin (300 mcg.…”
Section: Methodsmentioning
confidence: 99%